Effects of weather and hunting on wild reindeer population dynamics in Hardangervidda National Park. Issue 1 (24th November 2019) - Bargmann, Tessa; Wheatcroft, Edward; Imperio, Simona; Vetaas, Ole R.
Abstract: Wild reindeer have a range that extends across the circumpolar region. In the last few decades, however, populations of wild reindeer have been on the decline. The reasons for these declines are poorly understood, but are suggested to be linked to both local and global climatic factors, disease, and human interference. Hardangervidda plateau in Norway is home to the largest wild reindeer population in Europe, and is at the southern end of its European range. This population is therefore of particular importance, particularly in the light of climate change. We investigated how weather and hunting have affected the wild reindeer population in Hardangervidda over the last two decades. Our findings suggest that the wild reindeer population in Hardangervidda is most affected by winter temperature and hunting, where colder temperatures and lower harvest rates typically result in higher growth rates. We did not find significant evidence for linear density dependence. Our results show trends across Hardangervidda, and give an indication of how region‐wide weather and hunting pressure can affect the wild reindeer population. As new data emerge, future investigations should look into the existence and nature of density dependence and the influence of other weather and human disturbance related factors. Abstract : We investigated how weather and hunting have affected the wild reindeer population in Hardangervidda over the last two decades. Our findings suggest that the population is most affected by winter temperature and hunting. Our results show trends across Hardangervidda, and give an indication of how region‐wide weather and hunting pressure can affect the wild reindeer population. The photographer Olav Strand gave his permission to use the GTOC image.